An SiO2/ZnBr2 mediated expeditious approach to 3-methyl-1-phenyl-1H-pyrazol-5(4H)-one derivatives in water under microwave irradiation1. Issue 1 (21st December 2015) - Parveen, Mehtab; Azaz, Shaista; Malla, Ali Mohammed; Ahmad, Faheem; Ahmad, Musheer; Gupta, Mayank
Abstract : An efficient and eco-friendly synthesis of pyrazolone derivatives. Abstract : A new one-pot three-component green approach has been developed for the synthesis of a series of pyrazolone derivatives2(a–s) from differently substituted aromatic aldehydes, ethylacetoacetate and phenylhydrazine/2, 4-dinitrophenylhydrazine in excellent yields (94–98%), employing SiO2 /ZnBr2 as a recyclable Lewis acid catalyst in water under microwave heating. The molecular structure of compounds2a and2d were well supported by single crystal X-ray crystallographic analysis. The present protocol bears a wide substrate tolerance and is believed to be more practical, efficient, eco-friendly and compatible as compared to existing methods.